If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x = 36 + 3x Solving 7x = 36 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7x + -3x = 36 + 3x + -3x Combine like terms: 7x + -3x = 4x 4x = 36 + 3x + -3x Combine like terms: 3x + -3x = 0 4x = 36 + 0 4x = 36 Divide each side by '4'. x = 9 Simplifying x = 9
| 6/10t=-6 | | -5(6x-7y+1)= | | 2x^2+33x-8.9= | | 43.6x-29.4=-3.5x | | 6x^2y^3-12xy^3+6y^3=0 | | l-6r=-4-3r | | X^(2/3)=8 | | F^1(x)=2sinx | | 5x^4+15x^2-50=0 | | 2/5+1/3t=2 | | 7a-35=7(7a+7) | | -8*-2y=10 | | 4t-41=2t+7 | | -4+5u-2(6u-11)= | | 6(3+6x)=20 | | m+5=m-6 | | 5+5=6+9 | | 2.2+5.2-7.3= | | (8+3i)-(2+4i)=0 | | -k+14=-4-2(2k-3) | | -3(2x+5)=-3 | | -4(4x+3)=2(5-8x)-22 | | x+23y=-15 | | 9q+5(8+2q)=0 | | 7+4(6+2-7)= | | 9q+5(8+2q)= | | 5a-9=29 | | -35x+42= | | f(x)=3x^2-18x+1 | | .666x=180 | | 5/8x=17 | | x^3-x^2-75/8=0 |